Determinants of rural households’ income inequality in India - Ghanshyam Pandey; Bisla Devi (Agricultural Economics Research Review, 2024)
This study has identified the drivers of income inequality in rural India using IHDS 2011–12 national-level survey. The inequality decomposition methodology developed by Fields (2003) based on a two-way regression methodology has been used. The study has modified on the previous regressionbased inequality decomposition technique by accounting for diverse income sources and regimes as well as by effectively correcting for selectivity in the various income regimes. The CLAD model has been used to distinguish the determinants of income inequality in rural India. The study has indicated that income inequality in farm households can be attributed to the level of education, family size, caste/social group composition, and composition in land ownership, and that family size and land ownership are instrumental primarily due to off-farm labour income. The study has shown that education is a significant factor in income inequality due to its impact on off-farm work income. The study has suggested that a continued increase in variability in land distribution may exacerbate income inequality in households in rural India.